2019
DOI: 10.3390/ijms20194667
|View full text |Cite
|
Sign up to set email alerts
|

Increased ROS Scavenging and Antioxidant Efficiency of Chlorogenic Acid Compound Delivered via a Chitosan Nanoparticulate System for Efficient In Vitro Visualization and Accumulation in Human Renal Adenocarcinoma Cells

Abstract: Naturally existing Chlorogenic acid (CGA) is an antioxidant-rich compound reported to act a chemopreventive agent by scavenging free radicals and suppressing cancer-causing mechanisms. Conversely, the compound’s poor thermal and pH (neutral and basic) stability, poor solubility, and low cellular permeability have been a huge hindrance for it to exhibit its efficacy as a nutraceutical compound. Supposedly, encapsulation of CGA in chitosan nanoparticles (CNP), nano-sized colloidal delivery vector, could possibly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 115 publications
(177 reference statements)
2
10
0
Order By: Relevance
“…The smallest nanoparticle size of CNP obtained from this study was 82.24 ± 2.67 nm which by using 250 uL TPP while PCNP was 90.23 ± 2.67 nm by using 200 uL TPP. This result was congruent with the findings of Kavi Rajan et al where the optimum chitosan to TPP ratio of about 3:1 [ 46 ]. Thereafter, particle size increased exponentially, indicating the formation of aggregates and nanoparticle clusters after this threshold resulting in the existence of excess TPP in the aqueous system, which may promote further interaction between the CNPs/pCNPs, thus initiating agglomerated nanoparticles with larger sizes [ 47 , 48 ].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The smallest nanoparticle size of CNP obtained from this study was 82.24 ± 2.67 nm which by using 250 uL TPP while PCNP was 90.23 ± 2.67 nm by using 200 uL TPP. This result was congruent with the findings of Kavi Rajan et al where the optimum chitosan to TPP ratio of about 3:1 [ 46 ]. Thereafter, particle size increased exponentially, indicating the formation of aggregates and nanoparticle clusters after this threshold resulting in the existence of excess TPP in the aqueous system, which may promote further interaction between the CNPs/pCNPs, thus initiating agglomerated nanoparticles with larger sizes [ 47 , 48 ].…”
Section: Resultssupporting
confidence: 93%
“…The particle size of pCNP-PCA increased from 90.2 to 196.3 nm, a 117.6% surge from empty pCNP. As this expansion correlated with previous study [ 46 ], the inclusion of a hydrophobic moiety within pCNP-PCA has affected its expansion compared to CNP-PCA at similar PCA concentrations used for encapsulation. This was ascribed to an increased amount of PCA encapsulated in pCNP-PCA, due in part towards a tighter hydrophobic-hydrophobic interaction forming between the palmitoyl groups in pCS with PCA prior to nanoparticle formation.…”
Section: Resultssupporting
confidence: 87%
“…Surely, the restricted solubility and permeability have always hindered the CGA efficacy as a nutraceutical compound. More recently, CGA encapsulation in a nano-sized colloidal delivery vector has been proposed as a possible approach to enhance its antioxidant properties and increase chemopreventive efficacy at an even lower concentration [64]. Moreover, even though an initial CGA Phase I clinical trial has recently been concluded, demonstrating that its injection is safe and well-tolerated in recurrent high grade glioma patients, collecting safety data in a larger statistical sample is absolutely necessary to define the tolerance and pharmacokinetics of this compound (NCT02245204).…”
Section: Discussionmentioning
confidence: 99%
“…Among numerous attempts to develop such a capacity, nanoencapsulation has been extensively exploited as a novel strategy to deliver anti-cancer drugs particularly for flavonoid phytochemicals due to their poor bioavailability [43,44]. The use of chitosan, rebaudioside A, and directly loading onto gold nanoparticles all have been shown to be feasible approaches and profoundly enhance the anti-cancer activity of chlorogenic or hesperidin [45][46][47][48]. With this concept in mind, our next endeavor is to encapsulate our herbal compounds with chitosan or nanolize chlorogenic acid and hesperidin via dry-heating treatment [49] to assess the delivery efficacy and therapeutic improvement in a murine model.…”
Section: Discussionmentioning
confidence: 99%